El rincón de lectura para el desarrollo del lenguaje oral en los niños y niñas de primer año de Educación General Básica de la Unidad Educativa Pedro Carbo, perteneciente a la parroquia Veintimilla, cantón Guaranda provincia Bolívar, período 2018-2019 - Galeas Orta, Elena Johana (2018)
The corners of learning since 2015 are implemented in early education, giving greater importance to work in spaces adapted and implemented with exclusive materials for each area which become stimulating specific intelligences and at the same time interrelated. The reading corner is undoubtedly the most important of the spaces since it creates the indispensable bases for writing and reading that is at the same time the basis of the education of the human being. In the reading corner, expressiveness develops, especially oral expression, since from the reading of images the boy and girl learn to express themselves and communicate messages replicating what catches their attention. By intervening applying strategies that change the reality found, it is clear that children in the reading corner enjoy reading images, getting familiar with texts that they will have to use throughout their lives, use new vocabulary, express themselves more easily and fluently. . The design of these environments is based on the principles of simplicity, beauty and order. They are luminous and warm spaces, which include plants, art, music and books (Salanova, 2007). In the reading environment books should not be absent and the best are the stories. In the reading corner the teacher will be able to develop the language to the maximum in the children of the level, planning diverse and fun strategies so that the learning is pleasant, significant and lasting.